Assessment of GFP Tag Position on Protein Localization and Growth Fitness in Yeast. Issue 3 (1st February 2019) - Weill, Uri; Krieger, Gat; Avihou, Zohar; Milo, Ron; Schuldiner, Maya; Davidi, Dan
Abstract: While protein tags are ubiquitously utilized in molecular biology, they harbor the potential to interfere with functional traits of their fusion counterparts. Systematic evaluation of the effect of protein tags on function would promote accurate use of tags in experimental setups. Here we examine the effect of green fluorescent protein tagging at either the N or C terminus of budding yeast proteins on subcellular localization and functionality. We use a competition-based approach to decipher the relative fitness of two strains tagged on the same protein but on opposite termini and from that infer the correct, physiological localization for each protein and the optimal position for tagging. Our study provides a first of a kind systematic assessment of the effect of tags on the functionality of proteins and provides a step toward broad investigation of protein fusion libraries. Graphical Abstract: Highlights: Protein tags are widely used in molecular biology, although they may interfere with protein function. The subcellular localization of hundreds of proteins in yeast is different when tagged at the N or the C terminus. A competition-based assay enables systematic deciphering of correct tagging terminus for essential proteins. The presented approach can be used to derive physiologically relevant tagged libraries.